KONSEP PENDIDIKAN KARAKTER DALAM PEMBELAJARAN - Nidawati Nidawati (FITRAH: International Islamic Education Journal, 2023)
Character education is important in the world of education in Indonesia. Noble character, politeness, and religiosity are upheld and become the culture of the Indonesian nation. The role of religious education is very strategic in realizing the character formation of students. Religious education is a means of transforming knowledge in the religious aspect (cognitive aspect), as a means of transforming norms and moral values to shape attitudes (affective aspect), which plays a role in controlling behavior (psychomotor aspect) so as to create a complete human personality/student. Character education must be integrated into all learning activities that are summarized in a curriculum so that character education can be one of the right accesses in carrying out character building for the younger generation, especially students; students who have high knowledge equipped with faith and piety to God Almighty, have noble character, are capable, creative, independent, and become democratic and responsible citizens.